Spatial patterning and demography in Strandveld succulent Karoo : implications for biodiversity management - Cheney, Chad (Chad Crispian) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2004.